FACTORS AFFECTING INTENTION ON WHISTLEBLOWING: AN ANALYSIS ON MODERATED MODEL OF WHISTLEBLOWING CHANNEL - Putriana, Astia; Hariadi, Bambang; Prihatiningtias, Yeney Widya (Badan Pemeriksa Keuangan Republik Indonesia, 2018)
The purpose of this study is to examine and to provide empirical evidence of the effect of personal responsibility, personal cost and education on whistleblowing intention, as well as the impact of whistleblowing channel in influencing personal cost on whistleblowing intention. The populations of this study are civil servants (ASN) from financial department and procurement services department in Banjarmasin municipal government. The sample of this study are 104 respondents, obtained using saturated sampling technique. Questionnaire data of this research is analyzed using the Partial Least Squares (PLS). The result shows that civil servants consider their personal responsibility as they intend to blow the whistle. Yet, the study finds that personal cost and education have no effect on civil servant’s whistleblowing intention. The study also finds that whistleblowing channel is unable to moderate the effect of personal cost on whistleblowing intention. These findings help to obtain an insight regarding the policy that can improve whistleblowing intention.